Teachers engaged in research : inquiry into mathematics classrooms, grades pre-k-2 - Smith, Stephanie Z.; Smith, Marvin E. (Emerald Publishing Limited : IAP- Information Age Pub., 2006)
This volume was written primarily for teachers who have developed (or who are being encouraged to develop) an awareness of and commitment to teaching mathematics for understanding. The research findings presented in these chapters suggest instructional implications worthy of these teachers' consideration. Often, the authors in this volume describe instructional practices or raise issues that have the potential to broaden views of teaching and learning mathematics. These chapters provide interesting problems and tasks used in the authors' work that readers can use in their own classrooms.
Keywords: Mathematics -- Study and teaching (Early childhood) -- United States.; Mathematics -- Study and teaching (Elementary) -- United States.; Elementary school teaching -- Research -- United States.; Education -- Teaching -- Subjects -- Mathematics.; Early childhood care and education.; Teaching of reading, writing and numeracy.; Educational: Mathematics and numeracy.; elektronické knihy; electronic books